2023
DOI: 10.1177/21582440231197259
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Fear of Missing Out Moderate the Effect of Social Media Influencers on Their Followers’ Purchase Intention?

Thi Cam Tu Dinh,
Mengqi Wang,
Yoonjae Lee

Abstract: Social media influencers, a new type of opinion leader, are considered followers’ role models and strongly affect their attitudes and behaviors. Although their power on social media platforms is an emerging phenomenon, the studies exploring the impact of influencers’ endorsement of products on their followers’ buying intentions are still limited. By employing 272 respondents exposed to influencers, this study used PROCESS models to test hypotheses. The results demonstrate that the desire to mimic influencers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(136 reference statements)
0
0
0
Order By: Relevance
“…The findings of this study confirm gamification's positive impact on online buying intentions, echoing Petkov et al (2011), Yang et al (2019, Dinh et al (2023), Xu et al (2020), Wen et al (2014) and Doğan-Südaş et al (2023). Similary, gamification directly and indirectly affects buying intentions, with PEOU and social interaction playing crucial roles.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The findings of this study confirm gamification's positive impact on online buying intentions, echoing Petkov et al (2011), Yang et al (2019, Dinh et al (2023), Xu et al (2020), Wen et al (2014) and Doğan-Südaş et al (2023). Similary, gamification directly and indirectly affects buying intentions, with PEOU and social interaction playing crucial roles.…”
Section: Discussionsupporting
confidence: 70%
“…While empirical studies on gamification are mostly focused on its impact on the marketing of products and brands (i.e., Hsu & Chen, 2018;Lee & Jin, 2019;Milanesi et al, 2023;Tsou & Putra, 2023;Xi & Hamari, 2020), there are only a few studies that measure its effect on buying intention. However, the studies on buying intention mainly discuss the direct effect on consumer online purchase behavior (i.e., Dinh et al, 2023;Doğan-Südaş et al, 2023;Wen et al, 2014;Xu et al, 2020;Yang et al, 2019) without reference to other elements of buying intention including enjoyment and social interaction. According to Zhang et al (2021), the elements of gamification are positively associated with enjoyment and social interaction, leading to impulsive buying behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Followers' engagement refers to their audience's active involvement, interaction, and response to the content they share, including likes, comments, shares, and other forms of participation, indicating the influencer's level of connection and impact on their followers (Dinh et al, 2023). Past studies have suggested that individuals are more likely to be actively involved and interact with information when it is congruent with their self-concept (Dinh et al, 2023;Sinha & Srivastava, 2023). According to Fetais et al (2023), the significance of emotional content should not be underestimated since posts on social media platforms elicit positive feelings, resulting in greater engagement.…”
Section: Literaturementioning
confidence: 99%
“…In recent years, there has been a scholarly focus on comprehending the engagement exhibited by followers on social media networks. Followers' engagement refers to their audience's active involvement, interaction, and response to the content they share, including likes, comments, shares, and other forms of participation, indicating the influencer's level of connection and impact on their followers (Dinh et al, 2023). Past studies have suggested that individuals are more likely to be actively involved and interact with information when it is congruent with their self-concept (Dinh et al, 2023;Sinha & Srivastava, 2023).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation